2017
DOI: 10.1093/scan/nsx095
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol’s effects on emotionally motivated attention, defensive reactivity and subjective anxiety during uncertain threats

Abstract: Developing a better understanding of how and under what circumstances alcohol affects the emotions, cognitions and neural functions that precede and contribute to dangerous behaviors during intoxication may help to reduce their occurrence. Alcohol intoxication has recently been shown to reduce defensive reactivity and anxiety more during uncertain vs certain threat. However, alcohol’s effects on emotionally motivated attention to these threats are unknown. Alcohol may disrupt both affective response to and att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 44 publications
5
28
2
Order By: Relevance
“…Furthermore, high rates of relapse during early abstinence co-occur with frequent endogenous and exogenous unpredictability -for example, unpredictable onset and intensity of aversive withdrawal symptoms, uncertainty about abstinence efficacy, unexpected exposure to drug cues, opportunities to use, and changes in social networks. Finally, other research demonstrates that acute alcohol administration provides negative reinforcement selectively during unpredictable (but not predictable) stressors (e.g., Bradford et al 2013Bradford et al , 2017Hefner et al 2013).…”
Section: Stressors: Characteristics and Contextmentioning
confidence: 99%
“…Furthermore, high rates of relapse during early abstinence co-occur with frequent endogenous and exogenous unpredictability -for example, unpredictable onset and intensity of aversive withdrawal symptoms, uncertainty about abstinence efficacy, unexpected exposure to drug cues, opportunities to use, and changes in social networks. Finally, other research demonstrates that acute alcohol administration provides negative reinforcement selectively during unpredictable (but not predictable) stressors (e.g., Bradford et al 2013Bradford et al , 2017Hefner et al 2013).…”
Section: Stressors: Characteristics and Contextmentioning
confidence: 99%
“…For example, the stressors in the current task were temporally unpredictable, but real world stressors may incorporate unpredictability in alternative, often complex ways. For this reason, we have developed alternative laboratory tasks that manipulate how predictable the stressor may be with respect to probability (Hefner & Curtin, 2012), intensity (Bradford et al, 2013), or location (Bradford, Motschman, Starr, & Curtin, 2017). These features (e.g., probabilistic and temporal uncertainty) can be combined to increase stressor unpredictability (Moberg & Curtin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a programmatic series of experiments in our laboratory has demonstrated that single administrations of moderate doses of alcohol (e.g., dose yielding blood alcohol concentrations; BACs; between 0.08 -0.15%) temporarily reduce startle potentiation during uncertain stressors significantly more than certain stressors (Bradford et al, 2013(Bradford et al, , 2017Hefner et al, 2013;Hefner & Curtin, 2012;Moberg & Curtin, 2009). Furthermore, Kaye et al (2017) have proposed that chronic use of alcohol causes etiologically relevant stress neuroadaptations (see Koob & Volkow, 2010) that manifest as persistent exaggerated reactivity to uncertain stressors in patients with alcohol use disorder.…”
mentioning
confidence: 98%
“…As stressors and other emotionally evocative stimuli demand an organism's limited attentional resources (Blanchard et al, 2011;Robinson et al, 2015), the P3 to the benign auditory startle probe is subsequently attenuated (i.e., probe P3 suppression) in the presence of more threatening stimuli such as visual cues signaling threat of shock. We (Bradford, et al, 2017) and others (Nelson et al, 2015) have used probe P3 suppression as "relatively pure index" (Bradley et al, 2006) of emotionally motivated attention in experimental stressor paradigms that also include measurement of startle potentiation." received recent attention, no study to date has tested the effects of a pharmacological manipulation (e.g., alcohol) on responses to uncontrollable and controllable stressors.…”
mentioning
confidence: 99%
See 1 more Smart Citation